Calcaneal fracture fixation using a new interlocking nail reduces complications compared to standard locking plates – Preliminary results after 1.6 years. (August 2019) - Herlyn, Anica; Brakelmann, Anna; Herlyn, Philipp KE; Gradl, Georg; Mittlmeier, Thomas
Abstract: Introduction: Surgical treatment of displaced intra-articular calcaneal fractures using a standard extended lateral approach for plate fixation is frequently associated with substantial wound healing complications and infections. This matched pairs analysis compares the new minimally-invasive calcaneal interlocking nailing technique to standard locking plate fixation in terms of reduction capacity, complication rates, and functional outcomes. Methods: Forty feet in 38 patients (mean patient age 52.5 years, range 27–78) were treated with calcaneal locking nail (LN)(n = 20) or locking plate (LP)(n = 20) and followed clinically and radiologically for 20 months. Follow-up included radiological assessments and functional evaluations including the American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Score and the Foot Function Index (R-FFI). Results: Times for surgery were similar for both techniques (LN 93 min, range 34 to 175 vs. LP 101 min, range 53 to 305). Length of hospital stay was significantly lower in the LN group (7.6 days, range 3 to 14 vs. LP 11 days, range 6 to 37). Time away from work was shorter by 3.5 days in LN group. LP group had superior range of motion in plantarflexion, eversion, and inversion at follow-up, while LP patients were superior in demonstrating a secure heelstrike (79% vs. LN 58%) and fewer needed permanent walking aids. AOFAS and FFI scores revealed no differences for both groups. Radiographs indicated an adequate reconstruction in both groups, followed by a slight loss of reduction at follow-up (LP 4.7° postoperative vs. follow-up; LN 5.1°). The overall complication rate between groups was significant with 5% complications in the LN group vs. 50% in the LP group (5% deep infection, 35% impaired wound healing, 5% hardware breakage, 5% superficial wound infection; LN: 5% superficial wound infection). Conclusions: The new calcaneal interlocking nail shows promising results in terms of reduction capacity and safety. Use of the minimally invasive locking nail technique minimized the risk of postoperative wound complications and achieved superior functional outcomes compared with standard locking plate fixation via the extended lateral approach.